Polyelectrolyte complexes via desalting mixtures of hyaluronic acid and chitosan—Physicochemical study and structural analysis. (10th December 2016) - Lalevée, G.; Sudre, G.; Montembault, A.; Meadows, J.; Malaise, S.; Crépet, A.; David, L.; Delair, T.
Highlights: The controlled assembly of chitosan and hyaluronic acid was achieved. Physicochemical parameters of chitosan and the influence on the PECs were investigated. Different physical forms as colloidal suspensions and coacervates were obtained. The nanostructure of the different hyaluronic/chitosan complexes was investigated. Abstract: Polyelectrolyte complexes (PECs) were prepared from Chitosan (CS) and Hyaluronic Acid (HYA) homogeneous mixtures of aqueous solutions. The method consisted of preparing a homogeneous mixture of the two polysaccharides via charge screening at high salt concentrations. Then, the mixture was dialyzed, leading to the controlled self-assembly of the two polyelectrolytes. Critical parameters like the chitosan degree of acetylation ( DA ) and molar mass ( Mw ), the residual salt concentration and the molar charge ratio r = nNH3 + ( CS )/ nCOO − ( HYA ) accounted for the transition from homogeneous aqueous solutions to colloidal suspensions ( r = 0.1 ) or gel coacervates ( r = 0.5 ). The influence of the DA and Mw of CS was evaluated by visual observations, light scattering and rheological measurements. For low values of r, Small Angle X-ray Scattering (SAXS) experiments revealed that the HYA nanostructure was weakly affected by the presence of PECs. On the contrary, the structure was impacted when increasing r, revealing a heterogeneous aggregate morphology with ladder-like chain interactions.